Kejadian Leukorea Berdasarkan Pelaksanaan Manajemen Preventif Leukorea pada Remaja Putri - wahyu wijayati (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2023)
Preventive management of leukorrhea is essential especially for young women so that even if an incident of physiological leukorrhea occurs it does not cause discomfort and even the occurrence of other serious health problems and impacts not only physically but also on the psychology of young women in the future. Young women have a contribution in preparing the quality of the next generation who are reliable. The aim of the study was to find out the description of the incidence of leukorrhea based on the management of leukorrhea preventive management in the Pare District, Kediri Regency. Methods: Descriptive research using a questionnaire via Google Form with a total sampling (44 respondents in December 2021), data analysis using percentages. The results of the study: out of a total of 37 respondents (84%) who had experienced the highest distribution of leukorrhea there were 15 respondents (34%) in the good category; then with good and very good categories; each there are 11 respondents (25%); whereas out of a total of 7 respondents (16%) who had never experienced leukorrhea, there were 4 respondents (9%) in the moderate category; and there were 3 respondents (7%) in the good category in the implementation of leukorrhea preventive management. Conclusion: the highest incidence of leukorrhea has occurred in respondents in the good category in the implementation of preventive management of leukorrhea in young women in the Pare District, Kediri Regency, therefore it is always essential to monitor and refresh related to clean and healthy living habits by involving all parties in the young women's environment.